Vagal Innervation and Early Postoperative Ileus in Mice - Mueller, Mario H.; Karpitschka, Martina; Gao, Zhirong; Mittler, Sarah; Kasparek, Michael S.; Renz, Bernhard; Sibaev, Andrej; Glatzle, Jörg; Li, Yongyu; Kreis, Martin E. (Journal of gastrointestinal surgery, 2011)
Introduction Postoperative ileus is characterized by infiltrates of leukocytes in the gut wall 24 h after surgery, which is subject to vagal modulation. We hypothesized that vagal modulation is irrelevant during earlier hours of postoperative ileus and aimed to determine whether afferent neuronal feedback to the central nervous system is altered by vagal innervation during this early period. Methods C57BL6 mice were laparotomized and received standardized small bowel manipulation to induce postoperative ileus. Subgroups were vagotomized 3–4 days prior to experiments while control animals were sham-operated. Three or 9 h later a 2-cm jejunal segment was harvested for multi-unit mesenteric afferent nerve recordings in vitro. Intestinal motility was monitored continuously and intestinal muscularis was stained for myeloperoxidase to determine infiltration of leukocytes. Results Peak amplitudes of intestinal motility and afferent nerve discharge at baseline were not different in all subgroups. Afferent discharge to 5-HT (500 μM) was virtually absent following vagotomy at 3 and 9 h of postoperative ileus (POI) compared to controls ( p < 0.05). Maximum afferent nerve discharge to bradykinin and peak firing during maximum distension at 60 mmHg was not different in all subgroups while luminal distension from 10 to 30 mmHg was lower at 3 h of POI following vagotomy compared to controls ( p < 0.05). The number of myeloperoxidase positive cells was similar at 3 h of POI in both subgroups; however, at 9 h of POI, ileus counts were increased to 713 ± 99 cells following vagotomy compared to 47 ± 6 cells per square millimeter in control animals. Conclusions Vagal afferents mediate sensitivity to low-threshold distension and 5-HT during postoperative ileus but not to high-threshold distension and bradykinin. Vagal inhibition of the intestinal immune response is present at 9 h but not detectable earlier, i.e., at 3 h of postoperative ileus when spinal reflex inhibition may prevail.